Culinary Heritage as a Means of Community Empowerment: a Study of Yu Sum’s Lenjongan Business - Septyani, Fatikha Indy; Nugrahani, Dian Ahimza; Septyani, Diyas; Yuliyanti, Gita (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This research aims to analyze the process of community empowerment through the culinary heritage of Lenjongan Yu Sum Business. This research uses a qualitative approach in the form of a case study using empowerment theory characterized by Zimmerman to find out the community empowerment process carried out by Lenjongan Yu Sum Business. Data were obtained through observation and in-depth interviews with the third heir of Lenjongan Yu Sum Business who became the research subject, as well as literature studies related to community empowerment. The results showed that the Lenjongan Yu Sum business has carried out an empowerment process from generation to generation on a small scale involving the surrounding community by expanding social and economic relations, as well as contributing to the preservation of traditional food. This is in accordance with Zimmerman's empowerment theory which explains that the empowerment process involves various actions that enable individuals or communities to gain control over their lives and improve their quality of life. This theory focuses on two main aspects, namely processes and outcomes. In this case study, the social process is seen through the inheritance of the business and recipes from generation to generation, as well as its collaboration with raw material suppliers and the surrounding community. The result of the process is the preservation of the original recipe from the first generation to the current fourth generation, so that Lenjongan Yu Sum still maintains its authentic taste. Thus, the Lenjongan Yu Sum business has been able to empower itself as well as have an empowering impact on the surrounding community.